Performance Analysis of the OneTouch® UltraVue™ Blood Glucose Monitoring System - Chang, Anna (Diabetes Technology Society, 2009)
BACKGROUND: OneTouch® UltraVue™ is a new meter for self-monitoring of blood glucose that includes a color display, used-strip ejector, and no-button interface. The system uses an electrochemical biosensor technology based on glucose oxidase chemistry to detect glucose concentrations from 20 to 600 mg/dl (1.1 to 33.3 mmol/liter). METHODS: Accuracy and reproducibility were evaluated over a wide range of glucose concentrations according to standard criteria. Clinical accu-racy was assessed by health care providers (HCPs) in two studies and by diabetes patients in the second study. Reference glucose lev-els were determined by a YSI 2300 analyzer. Same-day reproducibility and day-to-day reproducibility were also evaluated. RESULTS: In the accuracy studies, 99.7% and 98.7% of tests by HCPs and 97.0% of tests by patients were within ±15 mg/dl (±0.8 mmol/liter) of the YSI reference for blood glucose <75 mg/dl (<4.2 mmol/liter), and within ±20% for blood glucose ≥75 mg/dl (≥4.2 mmol/liter), respectively. Consensus error grid analysis showed that 99.7% and 95.3% of tests by HCPs and 97.0% of tests by patients fell within zone A (i.e., has no effect on clinical action); all other results were in zone B (i.e., altered clinical action, little or no effect on clini-cal outcome). In the reproducibility studies, the standard deviation was <1.5 mg/dl (<0.1 mmol/liter) for glucose concentra-tions <100 mg/dl (<5.6 mmol/liter), and the coefficient of variation was <2% for concentrations ≥100 mg/dl (≥5.6 mmol/liter). CONCLUSIONS: OneTouch UltraVue meets standard acceptability criteria for accuracy and reproducibility across a wide range of glucose concentra-tions. Its simple interface and lack of contact with used strips make it a viable option for older patients and their caregivers.